Myeloid‐Derived Suppressor Cell Membrane‐Coated Magnetic Nanoparticles for Cancer Theranostics by Inducing Macrophage Polarization and Synergizing Immunogenic Cell Death - Yu, Guang‐Tao; Rao, Lang; Wu, Hao; Yang, Lei‐Lei; Bu, Lin‐Lin; Deng, Wei‐Wei; Wu, Lei; Nan, Xiaolin; Zhang, Wen‐Feng; Zhao, Xing‐Zhong; Liu, Wei; Sun, Zhi‐Jun (Advanced functional materials, 2018)
A major challenge for traditional cancer therapy, including surgical resection, chemoradiotherapy, and immunotherapy, is how to induce tumor cell death and leverage the host immune system at the same time. Here, a myeloid‐derived suppressor cell (MDSC) membrane‐coated iron oxide magnetic nanoparticle (MNP@MDSC) to overcome this conundrum for cancer therapy is developed. In this study, MNP@MDSC demonstrates its superior performance in immune evasion, active tumor‐targeting, magnetic resonance imaging, and photothermal therapy (PTT)‐induced tumor killing. Compared with red blood cell membrane‐coated nanoparticles (MNPs@RBC) or naked MNPs, MNP@MDSCs are much more effective in active tumor‐targeting, a beneficial property afforded by coating MNP with membranes from naturally occurring MDSC, thus converting the MNP into “smart” agents that like to accumulate in tumors as the source MDSCs. Once targeted to the tumor microenvironment, MNPs@MDSC can act as a PTT agents for enhanced antitumor response by inducing immunogenic cell death, reprogramming the tumor infiltrating macrophages, and reducing the tumor's metabolic activity. These benefits, in combination with the excellent biocompatibility and pharmacological kinetics characteristics, make MNP@MDSC a promising, multimodal agent for cancer theranostics. Myeloid‐derived suppressor cell (MDSC) membranes are collected from tumor‐bearing mice and further used for magnetic Fe3O4 nanoparticle (MNP) coating. The resulting MDSC‐mimicking nanoparticles (MNP@MDSC) demonstrate superior performance in immune evasion, active tumor‐targeting, magnetic resonance imaging, photothermal therapy‐induced tumor killing, and excellent biocompatibility and pharmacological kinetics characteristics. These benefits make MNP@MDSC a promising, multimodal agent for cancer theranostics.